2017
DOI: 10.21078/jssi-2017-489-22
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualizing Mining of Firm’s Web Log Files

Abstract: In this era of a data-driven society, useful data (Big Data) is often unintentionally ignored due to lack of convenient tools and expensive software. For example, web log files can be used to identify explicit information of browsing patterns when users access web sites. Some hidden information, however, cannot be directly derived from the log files. We may need external resources to discover more knowledge from browsing patterns. The purpose of this study is to investigate the application of web usage mining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…From log files, we can use basic statistical analysis to find more information, but the knowledge extracted from this kind of analysis is very limited (Trakunphutthirak et al., 2017). Machine learning techniques enable us to extract more knowledge from this data: they allow us to mine the log file data to better understand and classify patterns in Internet usage behaviour.…”
Section: Some Related Workmentioning
confidence: 99%
“…From log files, we can use basic statistical analysis to find more information, but the knowledge extracted from this kind of analysis is very limited (Trakunphutthirak et al., 2017). Machine learning techniques enable us to extract more knowledge from this data: they allow us to mine the log file data to better understand and classify patterns in Internet usage behaviour.…”
Section: Some Related Workmentioning
confidence: 99%
“…Basic statistical analysis can be performed to discover more information from log files. The key problem with this analysis is that the knowledge extracted from this kind of analysis is very limited (Trakunphutthirak, Cheung, and Lee 2017). Many recent studies (Amornsinlaphachai 2016;Senthil and Lin 2017;Zhou et al 2018) have shown that machine learning techniques are mostly able to extract more knowledge from that data.…”
Section: Machine Data: Internet Access Log Filesmentioning
confidence: 99%
“…Firewalls automatically keep an internet access log file in a systematic way (Trakunphutthirak, Cheung, and Lee 2017). The log file is used to create a data model as a schema on read (Dong and Srivastava 2013).…”
Section: Introductionmentioning
confidence: 99%